KESENIAN KARAWITAN DALAM DIMENSI PENDIDIKAN KARAKTER DI SEKOLAH DASAR INKLUSI - Arief, Ardian; Fitriani, Ana (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2020)
The research descriptive aims to describe the implementation of character education through musical extracurricular activities in inclusive education schools in SD Siluk. The subjects of this study were the school principal, musical teacher, class teacher, special assistant teacher, and students. Data collection techniques using interviews, observation, and documentation. Data analysis techniques used are descriptive qualitative analysis with data analysis models according to Miller and Huberman. The result showed the 1) the implementation of character education through musical extracurricular activities at SD Siluk by shaking hands, picking up instruments in the box. Pray before & after the activity, students adhere to ethics in music. The use of lectures, questions, and answers, and practice methods. Provide exemplary & personal approach to students. Train to your confidence by taking part in the competition & performing arts. Clean up of gamelan and restore the instrument. 2) the dimensions of the development of inclusive education in karawitan include the dimensions of culture, policy, and practice. 3) character values formed are responsibility, love the motherland, appreciate achievement, cooperation, confidence. 4) Supporting factors are community leaders who have gamelan, using technology that supports musical activities, karawitan space is quitter extensive.